High molecular weight poly(butylene succinate-co-furandicarboxylate) with 10 mol% of BF unit: Synthesis, crystallization-melting behavior and mechanical properties. (November 2017) - Peng, Shuangbao; Bu, Zhiyang; Wu, Linbo; Li, Bo-Geng; Dubois, Philippe
Graphical abstract: Highlights: PBSF10 with M w as high as ∼200, 000 g/mol was synthesized. PBSF10 has the same crystal structure as PBS but larger amorphous region thickness. PBSF10 is less crystallizable than PBS but still exhibits rapid crystallization. The equilibrium melting temperature of PBSF10 is 122 °C. PBSF10 has superior tensile properties due to high M w and good crystallizability. Abstract: In this study, high molecular weight poly(butylene succinate-co-furandicarboxylate) with 10 mol% of butylene furandicarboxylate unit (PBSF10) was synthesized and its crystal structure and crystallization-melting behaviors were investigated by means of WAXD, SAXS, DSC and POM. The tensile properties were also assessed. The crystal structure of PBSF10 is found to be the same as that of poly(butylene succinate) (PBS). The SAXS result indicates that PBSF10 had the same thicknesses of crystalline region and transition zone, but larger thickness of amorphous region, indicating that the BF units are mostly excluded from the crystalline region and located in the amorphous region. Therefore, PBSF10 is less crystallizable than PBS. But PBSF10 still exhibits rapid nonisothermal and isothermal crystallization. Because of high molecular weight and good crystallizability, PBSF10 exhibits superior tensile properties: modulus 370 MPa, strength at break 38 MPa and elongation at break 230%.